Analysis Of Work Motivation In Increasing Employee Productivity At PT PLN (Persero) ULTG Panakkukang - Mawarni, Mawarni; Agus Salim HR; Andi Arifwangsa Adiningrat (CV. AFDIFAL MAJU BERKAH, 2024)
This study aims to analyze work motivation in increasing employee productivity at PT PLN (Persero) ULTG Panakkukang. This type of research is qualitative with data collection techniques used through observation and interviews. The object of this research is the manager and employees of PT PLN (Persero) ULTG Panakkukang, totaling 5 informants. The results of the research that can be written show that employees of PT PLN (Persero) ULTG Panakkukang are less motivated at work which has an impact on employee work productivity. This can be seen from the lack of encouragement in the form of incentives such as awards given by the company, employees feel the work given and the awards received are not balanced. The condition of the work environment that makes the lack of comfort of employees at work, because of the interaction between employees who are less harmonious and good communication so that employees are busy with their respective activities such as playing cellphones. Physical needs such as office facilities that still need attention such as office chairs and tables that have not been updated, office ac that has not been repaired, and this has an impact on the level of employee work motivation.